2022
DOI: 10.1007/s43657-021-00041-y
|View full text |Cite
|
Sign up to set email alerts
|

Optical Imaging of Epigenetic Modifications in Cancer: A Systematic Review

Abstract: Increasing evidence has demonstrated that abnormal epigenetic modifications are strongly related to cancer initiation. Thus, sensitive and specific detection of epigenetic modifications could markedly improve biological investigations and cancer precision medicine. A rapid development of molecular imaging approaches for the diagnosis and prognosis of cancer has been observed during the past few years. Various biomarkers unique to epigenetic modifications and targeted imaging probes have been characterized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…This inefficient form of energy metabolism supplies the need for new proliferating cancer cells and enables the use of intermediate products to yield biomolecules, such as amino acids, and nucleotides ( 8 ). Previous studies revealed that amino acids could have impacts on cell proliferation, the tumor microenvironment, epigenetic modification, and drug resistance ( 9 14 ). Previous studies also revealed that amino acid aberrant metabolism was associated with tumor progression and immune infiltration in ccRCC and other cancers ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…This inefficient form of energy metabolism supplies the need for new proliferating cancer cells and enables the use of intermediate products to yield biomolecules, such as amino acids, and nucleotides ( 8 ). Previous studies revealed that amino acids could have impacts on cell proliferation, the tumor microenvironment, epigenetic modification, and drug resistance ( 9 14 ). Previous studies also revealed that amino acid aberrant metabolism was associated with tumor progression and immune infiltration in ccRCC and other cancers ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetic abnormalities, epigenetic factors can also play a crucial role in tumor formation. The difference between epigenetic and genetic factors is that the former alters gene expression without changing DNA sequences and can be reversibly inherited [136,137].…”
Section: Mirnas and Epigenetics In Cllmentioning
confidence: 99%
“…In addition to genetic abnormalities, epigenetic factors can also play a crucial role in tumor formation. The difference between epigenetic and genetic factors is that the former alters gene expression without changing DNA sequences and can be reversibly inherited [136, 137]. Several important biological processes, including embryonic growth and cellular differentiation, are controlled by epigenetic factors [138].…”
Section: Introductionmentioning
confidence: 99%
“…In pursuit of early diagnosis and widespread implementation, obtaining blood samples proves to be a less invasive and more convenient alternative compared to tissue samples. Numerous cancer studies have revealed a significant association between cancer risk and DNA methylation in peripheral blood leukocytes, encompassing various types of tumors such as colorectal, bladder, gastric, breast, and head and neck cancers [ 7 12 ]. Recently, a diagnostic model for colorectal cancer (CRC) based on five methylation markers in peripheral blood mononuclear cells demonstrated the ability to identify colorectal patients earlier compared to conventional methods [ 13 ].…”
Section: Introductionmentioning
confidence: 99%